BENTUK, MAKNA DAN FUNGSI KESENIAN MOANGGO (NYANYIAN RAKYAT MASYARAKAT TOLAKI) - Evang Asmawati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aimed to analyze and describe the forms, meanings, and functions contained in the traditional art of Moanggo (a folksong of Tolakinese society) in Konawe regency. The study employed a qualitative method. The data of the study was oral data obtained from native speakers who know well about Moanggo. The targeted informants were those who hold good expertise/fluency with Moanggo and were living in Konawe regency. The techniques of data collection used in this study were: 1) recording, 2) note-taking, 3) elicitation. The techniques of data analysis involved transcription and translation, followed by heuristic and hermeneutic reading, and then finally interpreting the forms, meanings, and functions contained in the text of Moanggo. The study employed hermeneutic theory, structural functional theory, and semiotic theory. The results of the study showed that Moanggo takes some forms similar to poems. Moanggo has five forms: anggo mete’ia, anggo mosawa-sawa, anggo monda’u, anggo mombeperiri and anggo ndula-tula. The meanings of Moanggo are related to such themes as advice, religion, and love. Moanggo serves the functions as a way of expressing feeling, giving advice (education), entertaining, and preserving local culture. Keywords: forms, meanings, functions, traditional art of Moanggo.